Evaluasi Model CIPP pada Program Peningkatan Mutu Guru di MAN 2 Langkat Sumatera Utara - Syafaruddin Syafaruddin; Inom Nasution; Novita Sari (Universitas Pendidikan Mandalika, 2023)
This study aims to evaluate the MAN 2 Langkat North Sumatra teacher quality improvement program. This research used the CIPP model evaluative method with a qualitative approach. The subjects of this study were principals and teachers. Data collection techniques were obtained through interviews, documentation, and observation. Data analysis was carried out interactively, including data reduction, data presentation, and verification / drawing conclusions. The results of this study showed that: 1) Evaluation of the context of the teacher quality improvement program in MAN 2 Langkat met the requirements and criteria. 2) The quality of improvement program evaluation for teachers in MAN 2 Langkat met the criteria. 3) Several criteria were implemented to evaluate the quality improvement program process for teachers in MAN 2 Langkat. 4). Evaluation of the product of the teacher quality improvement program in MAN 2 Langkat in terms of mastery of curriculum material in 2013 for the teachers was good, and the target program was quite good.